Transverse colon volvulus in neurologicaly imparied patient as an emergency surgical condition – A case report - Miličković, Maja; Savić, Djordje; Stanković, Nikola; Vukadin, Miroslav; Vlahović, Aleksandar; Božić, Dejana (Vojnosanitetski pregled, 2017)
Introduction. Transverse colon volvulus is an uncommon cause of bowel obstruction in general. Predisposing factors are mental retardation, dysmotility disorders, chronic constipation and congenital megacolon. Case report. We presented transverse colon volvulus in a 16-year-old boy with cerebral palsy. Chronic constipation in neurologicaly impaired patient was a risk factor predisposing to volvulus. The patient was admitted to the hospital with enormous abdominal distension and acute respiratory insufficiency. A boy was emergently taken to the operating room for exploratory laparotomy. During the surgery, a 360º clockwise volvulus of the transverse colon was found. After reduction of volvulus, an enormous transverse colon was resected and colostomy was formed. In the postoperative period, despite the good functioning of stoma and intraabdominal normotension, numerous and long lasting respiratory problems developed. The patient was discharged from our institution after 8 months. Conclusion. Though very rare in pediatric group, the possibility of a transverse colon volvulus must be considered in the differential diagnosis of acute large bowel obstruction.